Kava (Piper methysticum G. Forst) for Substance Use Disorders: A Review of Mechanism, Pharmacology, Clinical Evidence, and Therapeutic Potential - Jason Krehl; Jessica Nissi Mamallapalli; Chengguo Xing; Oliver Grundmann (Nutrients, 2026)
Substance use disorders (SUDs) remain a major public health concern and contribute substantially to compromised quality of life, mortality, and healthcare burden. In the United States alone, millions of individuals are affected by alcohol use disorder (AUD), tobacco use disorder (TUD), and opioid use disorder (OUD), with many cases complicated by co-existing anxiety and stress-related disorders. Piper methysticum G. Forst (kava), a traditional South Pacific plant preparation, has gained attention for its anxiolytic, sedative, and sleep-promoting properties. Its pharmacological effects are primarily attributed to a set of lipophilic compounds known as kavalactones, which have been reported to modulate GABAA receptor activity, dopaminergic and adrenergic signaling pathways, monoamine oxidase-B activity, cannabinoid receptor type 1 activity, and voltage-gated ion channels. Peer-reviewed literature was identified through searches of PubMed, NIH resources, and other scientific databases using terms related to kava, kavalactones, addiction, anxiety, stress, insomnia, and SUDs. Both clinical and preclinical studies were reviewed, including investigations of neurotransmitter systems and addiction-related signaling pathways. The current literature suggests that the strongest rationale for kava use exists in AUD, where anxiety and stress are established contributors to relapse. Evidence supporting kava use in TUD and OUD is largely theoretical, while concerns regarding hepatotoxicity, cytochrome P450 interactions, product variability, and additive risk remain important barriers to its clinical application. In summary, current evidence does not support kava as a replacement for established therapies, while its unique pharmacological profile warrants further investigation as a potential adjunctive treatment for withdrawal and relapse in SUDs.